THE COMMUNITY HEALTH NURSING ASSESSMENT OF TUNJUNGSARI SUBURBAN, BANTUR VILLAGE, MALANG DISTRICT: A CASE STUDY - Mazarina Devi, Hilda; Soebagiono; Denik, Retno (Universitas Airlangga, 2024)
Background: The community health nursing assessment is a process to understand the health problems that are often found in such location including health behavior problems, environmental problem, also health services utilization problem which will cause various effect among age group population Purpose: Researcher would like to perform nursing process to the community health problems at the Tunjungsari Suburban, Bantur Village, Malang District. Methods: The case study with a cross sectional approach used as research design. The nursing community assessment checklist delivered to 641 respondents who lives at 217 households around Tunjungsari Suburban, Bantur Village. The data then analyzed using descriptive statistical analysis based on community nursing approach using community as partner theory. Results: The results showed that the community had a risky health behaviour marked by 47% adult were smoking inside the house, 73% of the elders never performing any health check, 89% of the elder's never to come to the Posyandu. 38,27% of the total population experienced acute inflammatory respiratory disease during the past 6 months, and failed to managing the household waste due to limited facilities. Conclusion: Based on the result of this study, it is recommended for the stakeholders to improve the community health services, increases the health promotion programs distribution especially targeting the elder's population. For the government providing final waste management in this community will help to increases the community health. Keywords: Case study; community health; nursing process.